Opening of Seven Enchantments: Transformative Initiative with Martopuro Village: Pembukaan Tujuh Pesona: Inisiatif Transformatif Gandeng Desa Martopuro - Sudarso, Satrio; Yusfian , Firli Perdana; Widya , Paramitha Puspa; Wati , Alvin Windiya (International Consortium of Education and Culture Research Studies, 2023)
The aim of this service is to: introduce and increase tourist awareness: introduce the unique charms of Martopuro Village to tourists and increase awareness of the various tourist attractions it offers. The service method carried out is Community Participation: Involving the local community in planning and implementing the program, ensuring active participation and a sense of community ownership of this initiative. The result of this service is increasing income. A larger number of visitors can increase income through the sale of local tourism goods and services. . The implication of this service is in the form of improving the image of the village, increasing the perception of Martopuro village as an attractive tourist destination, attracting investors, and supporting regional tourism promotion. Therefore, by increasing capacity, infrastructure and promoting the seven charms of local tourism, this project is expected to help develop and empower Martopuro Village. Highlight: Community Engagement: Involving locals in program planning and execution fosters a sense of ownership and active participation, vital for sustainable tourism development. Economic Impact: Increased tourist visits lead to improved income opportunities through the sale of local goods and services, boosting the village's economy. Tourism Promotion: Enhancing the village's image attracts investors and supports regional tourism, aiding in the development and empowerment of Martopuro Village. Keyword: The unique charm of the village, Tourist participation, transformative initiatives, society participation